Agent-based simulation for water resource management - Pereira, Julia P. C.; Adamatti, Diana F.; Barbosa, Raquel M. (Proceedings of the Workshop-School on Agents, Environments, and Applications (WESAAC); 2020: Proceedings of the 14th Workshop-School on Agents, Environments, and Applications, 2020)
This paper aims to present the study about the participatory management of water resources from simulations developed in the multiagent environment NetLogo. In this way, the work uses the NetLogo to simulate the modeled social situation that comprises active agents such as farmers, businessmen, mayors, councilors, members of NGOs and environmental inspectors in search of the management of their professional interactions in favor of the more efficient use and distribution of the water, with a view to reducing pollution with good practices. The multiagent system presented assumes a fundamental role in solving the proposed problem, providing relevant information and indicators for the study and prevention of the impacts of agriculture on the environment.